Spontaneous subdural hematoma in a multigravida with chronic kidney disease and superadded pre-eclampsia detected by MRI: a case report - Yadav, Preeti; Mukherjee, Arindam; Kumar, Rakesh (International Journal of Research in Medical Sciences, 2019)
Chronic kidney disease and pre-eclampsia are both known individual culprits for significant morbidity and mortality of mother and child worldwide. Non traumatic spontaneous subdural hematoma in pregnancy is a rare scenario, however stage 5 chronic kidney disease with superadded pre-eclampsia can be contributory factor for spontaneous extra axial bleed. Our patient was 25-year-old with history of end stage renal disease and chronic hypertension admitted with superadded pre-eclampsia. She had 1 living issue and 2 stillbirths. There was sudden deterioration of mental status as well as motor performance, the patient turned stupurous and was not following verbal commands. Patient was sent for MRI evaluation of brain and diagnosed as right sided subdural hematoma with significant midline shift towards the contralateral side. No intraparenchymal haemorrhage was noted.